Panhypopituitarism Presenting as Progressive Visual Acuity Deterioration Secondary to Suprasellar Germinoma - Young Po, Rainer Wandrew (J Endocr Soc, 2021)
Background: Overall the incidence of germ cell tumors worldwide is 0.1% with 60% comprising of germinomas. These may present in the suprasellar region a third of the time and thus impart variability in its presenting characteristics. Clinical Case: A 27-year male presented with progressive blurring of vision with incongruent visual acuity and refraction grade with optic disc pallor assessed with normal angiography. Patient also presented with increasing docility, sluggishness and more withdrawn behavior paired with polyuria, polydipsia and cold intolerance. Progressive worsening of vision led to cranial CT revealing an enhancing hyper density in the right caudate head later elucidated via MRI with several interspersed non-enhancing foci in the right caudate nucleus, both internal capsules with associated mild mass effect. The largest component located in the right capsular region with measurement of 21 x 21 x 16 mm with enhancing lesions in the hypothalamus and pituitary stalk. Endocrine evaluation revealed low serum cortisol at 91.03nmol/L (NV 138-685 nmol/L), responsive to ACTH stimulation test (65.94nmol/L to 387nmol/L), high prolactin at 856.9 mIU/L (42.4-296.8mIU/L) and low FT4 8.62pmol/l (9.01-19.05 pmol/L) despite normal TSH 1.528uIU/ml (0.35-4.94 uIU/mL). Optic nerve atrophy was now attributed to compressive intracranial mass. Secondary adrenal insufficiency was managed with hydrocortisone 50mgIV every 8 hours, and central hypothyroidism was managed with levothyroxine 75mcgtab 1tab once a day. Increased urinary output assessed as diabetes insipidus was given desmopressin 60mcg/tab ½ tab 2x a day at this time. Stereotactic biopsy of the brain revealed a germinoma of the right caudate lobe. Given the nature of the intracranial mass with high sensitivity to chemotherapeutic and radiotherapy, a multidisciplinary approach to treatment was taken with radiotherapy, hormonal and steroid replacement. Patient underwent external beam radiation therapy of the brain and spine for a total of 51 treatments allowing for improvement of visual acuity to counting, with polyuria less than 2-3 diaper changes per day. Conclusion: Optic disc pallor is a clinical sign that indicates optic nerve atrophy reflective of the optic tract. This may be an important clinical sign to increase clinical suspicion for intracranial mass lesion especially with correlation to manifestation of pituitary hormone deficiencies.